Characteristics of global dispersion and mode distribution modeled for JT-60U like strongly reversed magnetic shear plasmas exhibiting L-modes with strong profile constraints - Rui Zhao; Kenji Imadera; Jianfu Liu; Wei Wang; Jiquan Li; Akihiro Ishizawa; Yasuaki Kishimoto (Nuclear Fusion)
The eigen-mode structure and distribution associated with the global dispersion are studied based on linear gyro-kinetic simulations in a global toroidal geometry using parameters and profiles modeled for JT-60U like discharges with a strongly reversed magnetic shear configuration, which exhibit L-mode characteristics subject to a strong profile constraint. By incorporating the mode mismatch parameter $Δ μ $ , related to the parallel wave number ${k_\parallel }\left( { \equiv {{Δ }}μ /{R_0}} \right)$ , and also the slab-to-toroidal ratio parameter $X\left( { \equiv {k_\parallel }{R_0}/{k_θ }{ρ _i}} \right)$ , we identified two qualitatively distinct unstable branches. One is the density gradient driven trapped electron modes ( $\nabla n$ -TEMs) influenced by the ion temperature gradient (ITG) with lower toroidal mode numbers $n$ , while transited to weak toroidal-like ITG modes as $n$ increases, in the inner negative magnetic shear region ( $\hat s < 0$ ). The other is the slab-like ITG modes with higher- $n$ in the outer minimum safety factor region ( $q\sim {q_{\min }}$ ). These dynamics result in the separate radial location of the density and ion/electron temperature gradients, i.e. the former is inner region while the latter is outer region. These two branches are weakly connected through the boundary region inside the ${q_{\min }}$ surface, which leads to a discontinuity in the quasi-linear flux. Each branch is found to show approximately the similar level of peak growth rate in inner and outer regions, indicating that the constrained profiles are expected to be established such that linearly unstable free energy sources are globally balanced so as to maintain such profile in a quasi-steady state with a self-organized manner without causing unbalanced transport.